The real Rosebud : the triumph of a Lakota woman - Weinberg, Marjorie, 1934- (University of Nebraska Press, 2004)
"Her great-grandfather was a famed Lakota warrior, her father a buffalo hunter, and Rosebud Yellow Robe hosted a CBS radio show in New York City. From buffalo hunting to the hub of twentieth-century urban life, this book chronicles the momentous changes in the life of a prominent Plains Indian family over three generations. At the center of the story is Rosebud (1907-92), whose personal recollections, family memoirs, letters, and stories form the basis of this book."--Jacket